Prevalence of exclusive breastfeeding and its related factors in Iran: A systematic review and meta-analysis - Azar Baba Ahmadi; Zahra Sadat Pajouhideh; Salmaz Mohammadi (Mashhad University of Medical Sciences, 2021)
Introduction: Breastfeeding is one of the most important strategies for the growth and survival of children, because it provides their physical, physiological and mental needs up to 6 months, so this review study was performed with aim to determine the prevalence of exclusive breastfeeding and its related factors in Iran. Methods: In this systematic review and meta-analysis study, the databases of Scopus, PubMed, web of science, SID, Magiran, Iranmedex, IranDoc and Google Scholar, the references of selected articles and unpublished sources (conferences, thesis) with the keywords of Breastfeeding, Exclusive, Prevalence and Iran were evaluated from 2010-2019. The Strobe checklist was used to assess the quality, the I2 index was used to assess the heterogeneity, and the Egger's test was used to assess the diffusion bias. The random effects model was used for the combined prevalence and odds ratio with 95% confidence interval. Data were analyzed by Stata software (version 16). Results: From 30 studies that their results were extracted, 19740 children were examined. The prevalence of exclusive breastfeeding was 0.49 (CI 95%; 0.38-0.59). The exclusive feeding odds ratio for type of delivery was 1.36 (CI 95%; 1.7-1.72), for education level was 1.36 (CI 95%; 1.01-1.84) and for maternal occupation was 2.15 (CI 95%; 1.09-4.23). Conclusion: The present study showed that the prevalence of exclusive breastfeeding was low and requires intervention measures.